Facilitation of L-type Ca2+ Currents by Fluid Flow in Rabbit Cerebral Artery Myocytes - Satoshi Amano; Tomohisa Ishikawa; Koichi Nakayama (Elsevier, 2005)
Blood vessels are receptive to hemodynamic forces, such as blood pressure and flow, which result in myogenic responses. The present study aimed to investigate the effect of mechanical stresses on L-type voltage-dependent Ca2+ channels in rabbit cerebral artery myocytes. Cell swelling induced by the exposure to a 16% hypotonic solution increased peak values of whole-cell Ba2+ currents (IBa). Similarly, an elevation of bath perfusion rate increased peak values of IBa. However, the response was reduced by the continued fluid flow stimulation and the current amplitude almost returned to the baseline. This reduction of the current was abolished by pretreatment with thapsigargin, implying the contribution of Ca2+ release from the sarcoplasmic reticulum to the response. These results suggest that L-type Ca2+ currents are facilitated not only by cell swelling but also by fluid flow in cerebral artery myocytes. Keywords:: L-type voltage-dependent Ca2+ channel, rabbit cerebral artery, patch clamp, swelling, flow